The Effect of Organizational Commitment on Employee Performance with Job Satisfaction as a Moderating Variable at PT. PLN (Persero) UP 3 Malang ULP Kepanjen - Aprilia, Renanda Riska; Irawati, Sandra; Robbie, R. Iqbal (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research aims to analyze the influence of organizational commitment on employee performance at PT. PLN (Persero) UP 3 Malang ULP Kepanjen with job satisfaction as a moderating variable. This research is of the type of explanatory research and is quantitative. The number of respondents in this research was 50 respondents and the data analysis used was using a range of scales, Partial Least Square (PLS), and Hypothesis Testing (Bootstrapping). The research results show that job satisfaction does not moderate the influence of organizational commitment on the performance of PT employees. PLN (Persero) UP 3 Malang ULP Kepanjen.